Chronic comorbidity of internal organs as a risk factor of complications and fatal outcome of community-acquired pneumonia. - Y. M. Mostovoy; A. V. Demchuk; T. V. Konstantynovych; K. D. Chichirelo-Konstantynovych (Medičnì Perspektivi)
With the purpose to estimate influence of comorbidity at the risk of complications and death due to community-acquired pneumonia (CAP) the retrospective analysis of 1587 case histories of inpatients with CAP (mean age – 48.5±18.4, males – 815 (51.4%), women – 772 (48,6%)) was performed. Comorbidity was observed in 1114 (70.2%). More frequently complications of CAP were developed in patients with chronic diseases than without them (p=0.013). Increased risk of pleural effusion was associated with chronic diseases of digestive system (OR=1.85 (95%CI 1.30-2.26)) and diabetes mellitus (OR=2.35 (95%CI 1.40-3.96)). Risk of sepsis development is higher in patients with nervous system diseases (OR=3.62 (95%CI 1.37-9.56) and drug or alcohol addiction (OR=19.08 (95%CI 7.30-49.82). Risk of pulmonary edema rose in patients with drug or alcohol addiction (OR=24.16; 95%CI 8.07-72.34), malignancy (OR=8.97; 95%CI 1.94-41.49), diabetes mellitus (OR=4.04; 95%CI 1.48-11.01), diseases of nervous (OR=4.04; 95%CI 1.17-13.94), urinary (OR=3.39; 95%CI 1.33-8.64) and cardiovascular (OR=2.29, 95%CI 0.98-5.34) systems. Higher risk of death in patients with CAP was associated with the presence of cardiovascular diseases (OR=2.17; 95%CI 1.11-4.25), diabetes mellitus (OR=2.95; 95%CI 1.20-7.21), drug or alcohol addiction (OR=38.40; 95%CI 15.05-97.98).